Cytokine adsorption is a promising tool in the therapy of hemophagocytic lymphohistiocytosis. Issue 11 (November 2019) - Frimmel, Silvius; Hinz, Michael; Schipper, Jan; Bogdanow, Simon; Mitzner, Steffen; Koball, Sebastian
Hemophagocytic lymphohistiocytosis is a life-threatening clinical syndrome caused by severe hypercytokinemia brought on by a highly stimulated but ineffective immune response. Animal studies and case series have demonstrated that a reduction in blood cytokine levels achieved with an extracorporeal adsorption cartridge that contains blood-compatible porous polymer beads (CytoSorb ® ) can effectively attenuate the inflammatory response during sepsis and possibly improve outcomes. We report a case series of two patients in which three episodes of severe hemophagocytic lymphohistiocytosis triggered by infections with herpesviridae were treated successfully with cytokine adsorption. A marked decrease in interleukin-6 plasma levels and a stable or decreasing need of vasopressor therapy were the most significant results of this treatment. Importantly, treatment was safe and well-tolerated, without any adverse events.